Preparation of a Selective Electrode Based on a Modified Carbon Paste for Determination of Phenol in Water Solutions and Study it’s by Potential Method - هاجر نصر ناصر; خليل ابراهيم العبيد (Latakia University Journal -Basic Sciences Series, 2022)
This research deals with the preparation of a selective electrode to determine phenol in standard and aqueous solutions using a modified carbon paste and use it as a working electrode. preparation modified carbon paste from away mixed by 3% , 1% Fe2O3 , 47.5 % graphite powder in addition to 48.5% paraffin oil (as plasticizer) . The proposed phenol electrode operates at pH = 7 and achieves linearity and a Nernst slope , and R² = 0.998, the linearity ranged between (10-6-10-3) M and the recoverability R% between (94.991- 107.446) %.The percentage relative standard deviation ranged between (3.94966-5.20372) %, which indicates the same correctness and accuracy of the method used. The proposed electrode works at the laboratory temperature 25∓3 and with a response time not exceeding (20) sec, and with a fixed time ranging up to (37) sec, as according to the t-test, and the experimental value was less than t- tab therefore the method is considered to have good reliability, the limit of detection LOD for the proposed method was 0.0283 mg/L. The limit of Quantification LOQ equal to 0.0954 mg/L, the results of the proposed method were compared with a reference method in the visible based on the Folin-Cicalto Reagent FCR, and calculating the value of F-test and comparing it with at 95% confidence level, it was found that there is not difference between the two methods, and when The were two methods applicated on a sample of drinking water from the city of Latakia showed that the quantity The phenol content is less than the quantitative detection this limit for them. The proposed method is characterized by its ease, simplicity and relatively low cost.